Teaching the Material on Work and Energy Using an Integrated Flipbook Emodule with the Qur'an to Improve Spiritual Attitudes and Learning Outcomes of Students at SMA Muhammadiyah 1 Pontianak - Ardi, Ardi; Djudin, Tomo; Habellia, Ray Cinthya (Devotion : Journal of Research and Community Service, 2026)
This study aims to test how learning business materials and energy assisted by the integrated flipbook e-module of the Qur'an to improve the spiritual attitude and learning outcomes of students at SMA Muhammadiyah 1 Pontianak. This study used a nonequivalent control group design, with a sample of 38 students of class X of MIPA 1 and 38 students of class X of MIPA 2. The instruments used in this study are tests and questionnaires of spiritual attitudes, using measurement techniques and questionnaire filling techniques. Data analysis was carried out to determine the influence of learning business materials and energy assisted by the Qur'an's integrated flipbook e-module on students' spiritual attitudes and learning outcomes. The results of the study showed that there were differences in spiritual attitudes and learning outcomes before and after learning business and energy materials assisted by the Qur'an-integrated flipbook e-module. The average spiritual attitude score of the experimental class before treatment was 37.26 increased to 65.92 after treatment. The average pretest score of 30.52 increased to 73.87 in the posttest. Furthermore, the effect size score of spiritual attitudes is 5.21 and learning outcomes are 1.56 so that learning of business and energy materials assisted by the integrated flipbook e-module of the Qur'an affects the spiritual attitude and learning outcomes of students. Thus, the integrated physics learning of the Qur'an must be applied in learning at school because it can arouse students' enthusiasm in learning.